Model Pembelajaran Problem-based Learning (PBL) dalam Pelajaran Matematika di Sekolah Dasar - Lukman Nul Hakim (Universitas Sebelas Maret, 2022)
The important role of math lessons in learning. In learning mathematics, steps are needed that can stimulate students to think critically. With this concept, it is hoped that the achievement of learning will be better and as expected. Efforts that can be made by a teacher in supporting the achievement of an innovative and meaningful learning, namely by designing and implementing a learning that is able to trigger curiosity, scientific and social behavior of students. One of the references of oriented learning model is Problem Based Learning. This research is literature research that describes: definition, objectives, syntax/learning steps, and advantages & disadvantages of the Problem Based Learning model, especially in elementary/middle school mathematics subject matter. Problem Based Learning is a recommended learning model in learning Mathematics at the SD/MI level because this model can support the increase of students' higher order thinking skills through investigation and problem solving and the development of students' knowledge construction.